Voltaire's Candide or The Optimist and Rasselas Prince of Abyssinia - Samuel Johnson; Henry Morley (UK George Routledge & Sons, 1884)
Voltaire's Candide and Johnson's Rasselas
Keywords: Literature (3GdCOHs; General